Savage spawn: reflections on violent children - Kellerman, Jonathan (The library of contemporary thought, 1999)
"In this book, author and child psychologist Jonathan Kellerman shines a penetrating light on antisocial youth - kids who kill without remorse - asserting that "psychopathic tendencies begin very early in life, as young as three, and they endure." Criticizing our quick impulse to blame violent movies or a "morally bankrupt" society, Kellerman convinces us that it is the kids themselves who need to be examined." "How do children become cold-blooded killers? Kellerman warns that today's aggressive bully is tomorrow's Mafia don, cult leader, or genocidal dictator. Violently psychopathic youths possess an overriding need for power, control, and stimulation, and all display a complete lack of regard for the humanity of others. He examines the origins of psychopathy and the ever-shifting debate between nurture and nature, offering some controversial solutions to dealing with homicidal tendencies in children."--BOOK JACKET